ByzRev 06.2024.055: Heather A. Badamo, Saint George Between Empires: Image and Encounter in the Medieval East.: University Park: Pennsylvania State University Press 2023. - Grotowski, Piotr Ł. (The Byzantine Review, 2024)
Heather A. Badamo, Saint George Between Empires: Image and Encounter in the Medieval East. University Park: Pennsylvania State University Press 2023. 264 pp., 24 color and 48 b&w ill., 3 maps. – ISBN 978-0-271-09522-6